Exploring the relationship between far-right online cultural and political activism with physical space. Examples from an island of the North-eastern Aegean - Petrou, Michael (The Greek Review of Social Research, 2023)
The paper aims to investigate the relationship between far-right political culture and ideology, as being developed on social media, and their social influence in the public space. Based on field research findings on the island of Lesvos in the fall of 2021, it attempts to clarify how far-right political and cultural activism via online social media and information interferes with, interacts and feeds far-right activism in the physical space.